Relationship Between Knowledge And Adolescent Attitudes Towards Communicable Sexual Hiv / Aids Diseases In Senior Hight School Tigapanah - Sinaga, Rosmani; Barus, Sarinem; Pinem, Srilina (Mitra Husada Health Internasional Conference (MIHHICo), 2023)
Reproductive health is a state of complete physical, mental, and social well-being, which is not merely free from disease or disability, in all matters relating to the reproductive system, and its functions and processes. The aim of adolescent reproductive health programs is to help adolescents to understand and be aware of the knowledge so that they have healthy attitudes and behaviors and are certainly responsible for their relationship with reproductive life issues. The purpose of this study was to determine the relationship of knowledge and attitudes of adolescents to HIV / AIDS sexually transmitted diseases in Senior Hight School Tigapanah in 2019. Sexually transmitted diseases (STDs) are disorders / diseases that are transmitted from one person to another through direct contact or sexual relations. The total population in SMA Negeri 1 Thirteen is 66 people with details of 33 class X people, 33 class XI people, the authors take some individuals from a population. And the research results obtained p = 0,000 there is a relationship between knowledge and attitudes of adolescents towards HIV / AIDS sexually transmitted diseases in Senior Hight School Tigapanah.